Developing an Android-Based English Reading Material for the Eighth Grade Students in Mtsn Karangasem - Rahmanita, Risci Ayu; Ratminingsih, Ni Made; Juniarta, Putu Adi Krisna (STKIP AGAMA HINDU SINGARAJA, 2021)
This study intended to find out the needs of the eighth-grade students in learning English and to develop an android-based application for learning English reading material in MTsN Karangasem. This study used the design and development research design model proposed by Richey & Klein (2014) which consisted of three major steps namely; 1) Design, 2) Development, 3) Evaluation. The subjects of this study were the eighth grade students of MTsN Karangasem, the English teacher in MTsN Karangasem, and integrated technology experts. The instruments used in this study were questionnaire, interview guide, and product evaluation sheets. The data were collected and analyzed qualitatively and quantitatively. The results showed that the students’ motivation to learn English was lack and need more learning resources or materials to learn reading comprehension. The eighth-grade students need a smartphone application that provides reading material learned in the class. The material developed in this study was limited to Recount Text material. The quality of the application got a high score from experts, which categorized in the excellent category. The use of the effective application with meaningful learning activities for learning reading comprehension for the eighth-grade students is strongly suggested